Cell Damage Index as Computational Indicator for Blood Cell Activation and Damage. Issue 7 (2nd April 2018) - Gusenbauer, Markus; Tóthová, Renáta; Mazza, Giulia; Brandl, Martin; Schrefl, Thomas; Jančigová, Iveta; Cimrák, Ivan
Abstract: Shear‐induced hemolysis is a major concern in the design and optimization of blood‐contacting devices. Even with a small amount of mechanical stress, inflammatory reactions can be triggered in the cells. Blood damage is typically estimated using continuum fluid dynamics simulations. In this study, we report a novel cell damage index (CDI) obtained by simulations on the single‐cell level in a lattice Boltzmann fluid flow. The change of the cell surface area gives important information on mechanical stress of individual cells as well as for whole blood. We are using predefined basic channel designs to analyze and compare the newly developed CDI to the conventional blood damage calculations in very weak shear stress scenarios. The CDI can incorporate both volume fraction and channel geometry information into a single quantitative value for the characterization of flow in artificial chambers.